Answer:
see explanation
Explanation:
Given
3x² - 5x + 2 = 0
Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term
product = 3 × 2 = 6 and sum = - 5
The factors are - 3 and - 2
Use these factors to split the x- term
3x² - 3x - 2x + 2 = 0 ( factor the first/second and third/fourth terms )
3x(x - 1) - 2(x - 1) = 0 ← factor out (x - 1) from each term
(x - 1)(3x - 2) = 0
Equate each factor to zero and solve for x
x - 1 = 0 ⇒ x = 1
3x - 2 = 0 ⇒ 3x = 2 ⇒ x =
![(2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jgft8n5xwx5uidfnxss9gbutm3s8nfmtko.png)
Roots are x = 1, x =
![(2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jgft8n5xwx5uidfnxss9gbutm3s8nfmtko.png)